HUBUNGAN ANTARA KOMPETENSI PROFESIONAL GURU DENGAN HASIL BELAJAR IPA SISWA KELAS V SD GUGUS II KECAMATAN TANETE RIATTANG KABUPATEN BONE - Iswandi Iswandi; Muhammad Amran; Satriani DH; Rasmi Djabba (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
Abstract; The problem in this study is the teacher's lack of understanding of the professional competence of teachers, namely broad and deep mastery of the material, as well as the effective use of media and learning facilities. This research is a quantitative research with a correlation design that aims to describe the professional competence of teachers with learning outcomes in science for class V Cluster II students. The results of this study indicate that there is a significant relationship between teacher professional competence and science learning outcomes in elementary school cluster II with a greater t_count (4.050) value (>) t_value (table )(1.68830) at a significance level of 5%. Thus H0 is rejected H1 is accepted. Based on the results of the data analysis above, it can be concluded that professional competence will have an impact on students' science learning outcomes. So the better the professional competence of the teacher, the better the student learning outcomes. From these conclusions, the impact resulting from this study is known that good professional competence will improve student learning outcomes.